2015
DOI: 10.4238/2015.may.4.15
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic analysis of African swine fever virus based on the p72 gene sequence

Abstract: ABSTRACT. African swine fever virus (ASFV) outbreak has been considered as an emerging and re-emerging disease for almost a century. Diagnostically, simple polymerase chain reaction and sequencing-based molecular detection could be employed for both viral identification and genotyping. This study established a novel phylogenetic analysis and epidemiology comparison based on 205 bp of p72 gene sequences. Based on this partial p72 fragment, an updated list of 44 different genotypes from a total of 516 ASFV seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 33 publications
0
19
0
1
Order By: Relevance
“…Muangkram et al . ( 52 ) established a novel phylogenetic analysis and epidemiological comparison based on VP72 gene sequences. They found that 516 sequences of ASFV compiled from GenBank belonged to 44 different genotypes, and ASFV populations of the African continent could be divided into four clades by the analysis of spatial genetic variation.…”
Section: P72 Proteinmentioning
confidence: 99%
“…Muangkram et al . ( 52 ) established a novel phylogenetic analysis and epidemiological comparison based on VP72 gene sequences. They found that 516 sequences of ASFV compiled from GenBank belonged to 44 different genotypes, and ASFV populations of the African continent could be divided into four clades by the analysis of spatial genetic variation.…”
Section: P72 Proteinmentioning
confidence: 99%
“…Molecular surveillance of ASFV is an integral part of the disease intervention activities in Europe and Africa. Most published studies used molecular characterization of vp72 or/and CVR gene segments for genotyping, subgrouping close related isolates, [ 11 , 29 – 31 ] and investigating the molecular epidemiology of the virus using traditional phylogenetic methods, such as neighbour-joining or maximum likelihood techniques [ 9 , 32 34 ]. Furthermore, such studies draw conclusions on the evolutionary origins of isolates through examining the phylogenetic, spatial and temporal characters in an entirely separate analytical setting [ 33 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, p30 and/or p72 proteins are used as coating antigens in at least 3 commercial ELISA kits for ASFV antibody detection. Caution should be taken when using p72 protein for serological diagnosis because p72 genes are not conserved, especially at the C-terminal end (Achenbach et al, 2017;Boshoff, Bastos, Gerber, & Vosloo, 2007;Michaud, Randriamparany, & Albina, 2013;Muangkram, Sukmak, & Wajjwalku, 2015;Quembo, Jori, Vosloo, & Heath, 2018). In this study, by comparing the p30 protein sequences from 86 ASFV isolates, we found that 3 out of 4 linear epitopes of p30, including epitopes in antigenic regions 3 and 4 are highly conserved.…”
Section: Discussionmentioning
confidence: 74%